PENGARUH STRUKTUR MODAL DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2013 - 2017 - Cerlie, Siti Sofia; Makhdalena, Makhdalena; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This study was aimed to determine the effect of capital structure and dividend policy on firm value both simultaneously and partially in manufacturing sector companies listed on the Indonesia Stock Exchange for the 2013-2017 period. The population of this study was all manufacturing sector companies listed on the Indonesia Stock Exchange for the period 2013-2017 which have the necessary data, namely the capital structure, dividend policy and firm value, which amount to 14 companies. This study used secondary data sourced from ICMD (Indonesian Capital Market Directory). The technical analysis of the data used is multiple linear regression with the help of the SPSS program (Statistical Product and Service Solutions). The results of the study was indicated that the capital structure and dividend policy simultaneously influence the value of the company. Capital structure partially has a negative effect on firm value. While dividend policy has a positive effect on firm value.Key Words: Capital Structure, Dividend Policy, and Firm Value